Kinetics and thermodynamics of the dissolution of steel in 1 mol L−1 hydrochloric acid solution in the presence of Silene Marmarica as environmentally friendly corrosion inhibitor - O.A. Abdullatef (Egyptian Journal of Petroleum)
The dissolution of steel in 1 mol L−1 hydrochloric acid solution containing different concentrations of Silene Marmarica was studied at different temperatures 30, 35, 40 and 45 °C using potentiodynamic polarization and electrochemical impedance spectroscopy (EIS) techniques. The results showed that the presence of Silene Marmarica inhibits the corrosion of steel in 1 mol L−1 hydrochloric acid solution and the inhibition efficiency increased with the increasing concentration of Silene Marmarica. The Langmuir adsorption isotherm was used to calculate the thermodynamic parameter ΔGads° from experimental data obtained during the course of this research. The activation parameters Ea, ΔH∗ and ΔS∗ were calculated using the Arrhenius equation in conjunction with experimental data also acquired during the course of our studies.